(untitled) (Journal of Forest and Livelihood, 2009)
Although community forestry is recognised as a successful programme in terms of rehabilitating forest condition, its contributions to local community development are not recognised adequately by the national policies, legislations and regulatory frameworks. Drawing on the results of a survey of 1100 Community Forest User Groups (CFUGs), a rapid social analysis of 24 CFUGs, and the review of local development practices in the Koshi Hills, this article claims that the organisational scope of CFUGs is not just limited to forestry activities but encompasses a wide range of development activities. The CFUG as a development institution provides opportunities for exercising political agency for democratic and equitable governance, and could demonstrate the innovations on poverty reduction through community forestry. This is demonstrated through a) significant CFUG investment in livelihoods/development sector outside of forest development, b) wide?ranging collaborative actions between CFUGs and nonforestry stakeholders, and c) innovative initiatives of poverty reduction, and inclusive and deliberative governance. The findings present a clear opportunity for development agencies and policy makers to promote CFUGs as the institutional platform for pro?poor local development. Full text is available at the ForestAction website DOI: http://dx.doi.org/10.3126/jfl.v8i2.2310 Journal of Forest and Livelihood 8(2) February 2009 pp.78-92